Arbuscular mycorrhizal fungi enhanced resistance to low-temperature weak-light stress in snapdragon (Antirrhinum majus L.) through physiological and transcriptomic responses - Li, Wei; Wu, Haiying; Hua, Junkai; Zhu, Chengshang; Guo, Shaoxia (Frontiers in Plant Science, 2024)
Low temperature (LT) and weak light (WL) seriously affects the yield and quality of snapdragon in winter greenhouse. Arbuscular mycorrhizal fungi (AMF) exert positive role in regulating growth and enhancing abiotic stress tolerance in plants. Nevertheless, the molecular mechanisms by AMF improve the LT combined with WL (LTWL) tolerance in snapdragon remain mostly unknown. Here, the roles of AMF (Funneliformis mosseae + Glomus versiforme) on LTWL tolerance in snapdragon were studied via physiological and transcriptome analysis. It turned out that that inoculation with AMF effectively alleviated the inhibition caused by LTWL stress on snapdragon root development, AMF also significantly enhanced the contents of soluble sugars, soluble proteins, proline, thereby maintaining the osmotic adjustment of snapdragon. In addition, AMF alleviated reactive oxygen species damage by elevating the contents of AsA, and GSH, and the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), monodehydroascorbate reductase (MDHAR), and glutathione reductase (GR). RNA-seq analysis identified 2422 differentially expressed genes (DEGs) in the LTWL vs LTWLI group. An indepth analysis of these DEGs revealed that AMF regulated the expression of genes related to photosynthesis (photosystem I related proteins, photosystem II related proteins, chlorophyll a/b binding protein), active oxygen metabolism (POD, Fe-SOD, and iron/ascorbate family oxidoreductase), plant hormone synthesis (ARF5 and ARF16) and stress-related transcription factors gene (bHLH112, WRKY72, MYB86, WRKY53, WRKY6, and WRKY26) under LTWL stress. Thus, AMF inoculation improved snapdragon root development and LTWL tolerance by regulating physiological and molecular characteristics of osmotic regulatory substances, enzymatic and non-enzymatic antioxidant defense systems, and the expression of transcription factor genes, and auxin synthesis-related genes, and reducing reactive oxygen species damage. This study provides a theoretical basis for AMF in promoting the production of greenhouse plants in winter.